2004
DOI: 10.1074/jbc.m309689200
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Post-translational CCR8 Modifications and Their Influence on Receptor Activity

Abstract: Post-translational modifications of the extracellular portions of receptors located in the cell membrane can contribute to modulating their biological activity. Using a mutagenesis approach in which single or multiple Tyrto-Phe, Thr-to-Ala, Ser-to-Ala, and Asn-to-Gln substitutions were made at the appropriate positions, we analyzed the sulfation and glycosylation state of the murine CCR8 chemokine receptor, and the way in which these post-translational modifications affect CCR8 activity. A Y14Y15-to-F14F15 CCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
30
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 29 publications
2
30
0
Order By: Relevance
“…For other infectious diseases, including herpes, Toxoplasma, Neisseria, and HIV, these clones can serve as tools to further examine pathogens' modes of attachment or other aspects of their infectious cycles, which may involve a role for sulfation beyond heparan sulfate. Given the importance of sulfation in controlling the activity of certain G protein-coupled receptors (21)(22)(23)44), the availability of defined mutant cell lines defective in sulfation creates new opportunities that complement the mutation of putative sulfation sites in the receptors themselves. Should the HAP1 cell line prove amenable to differentiation into more specialized cell types (17), it may even be possible to explore tissue-specific aspects of sulfation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For other infectious diseases, including herpes, Toxoplasma, Neisseria, and HIV, these clones can serve as tools to further examine pathogens' modes of attachment or other aspects of their infectious cycles, which may involve a role for sulfation beyond heparan sulfate. Given the importance of sulfation in controlling the activity of certain G protein-coupled receptors (21)(22)(23)44), the availability of defined mutant cell lines defective in sulfation creates new opportunities that complement the mutation of putative sulfation sites in the receptors themselves. Should the HAP1 cell line prove amenable to differentiation into more specialized cell types (17), it may even be possible to explore tissue-specific aspects of sulfation.…”
Section: Discussionmentioning
confidence: 99%
“…Lacrimal gland development (17), viability and neural development in C. elegans (18), FGF-induced signaling (19), and cartilage homeostasis (20) all depend on sulfation. Sulfation of tyrosine residues is important for the interaction of chemokines and their receptors (21)(22)(23) and for binding and entry of HIV (24). Beyond studying interactions of bacteria with human host cells, the tools generated here can be used to investigate in tissue culture other processes in which sulfation may be important.…”
mentioning
confidence: 99%
“…In mammals, sulfation of tyrosine residues on cell surface proteins is important for the interactions of chemokines with certain chemokine receptors, and for viral binding and entry (1)(2)(3)(4)(5)(6). Sulfated glycans modulate processes such as leukocyte homing to lymph nodes, clearance of serum glycoproteins, and blood coagulation (7)(8)(9).…”
mentioning
confidence: 99%
“…This modification is catalyzed in the Golgi apparatus by the enzymes tyrosylprotein sulfotransferases 1 and 2, which preferentially sulfate tyrosine residues located near acidic residues (4), a motif found in the N-terminal regions of most chemokine receptors (3). The chemokine receptors CCR2, CCR5, CCR8, CXCR3, CXCR4, CX 3 CR1, and Duffy antigen and receptor for chemokines (DARC) have been demonstrated to contain sulfated tyrosine residues that modulate chemokine binding (5)(6)(7)(8)(9)(10)(11). Moreover, studies using differentially sulfated N-terminal peptides from various chemokine receptors have shown that tyrosine sulfation increases the binding affinity of the receptor peptides to their cognate chemokines (12)(13)(14)(15)(16).…”
mentioning
confidence: 99%